Wharton jelly-derived mesenchymal stem cell exosomes induce apoptosis and suppress EMT signaling in cervical cancer cells as an effective drug carrier system of paclitaxel - Abas, Burcin Irem; Demirbolat, Gulen Melike; Cevik, Ozge (PUBLIC LIBRARY SCIENCE, 2022)
Mesenchymal stem cells can be obtained and multiplied from various sources and have a very high capacity to release exosomes. Exosomes are nano-sized extracellular vesicles containing biological signaling molecules. This study aimed to determine the effect of MSC-derived exosomes as a drug delivery system for paclitaxel in cervical cancer cells. In this study, human MSC were isolated from wharton jelly of umbilical cord tissue (WJ-MSC), and cells were characterized by CD44, CD90, CD105, and CD34 staining. Exosomes were released in WJ-MSC cells with serum-starved conditions for 48 hours, and particle sizes and structures were examined with zeta-sizer and TEM. In addition, exosomes CD9, CD63, and CD81 markers were checked by western blot. Paclitaxel was loaded into exosomes (Exo-PAC) by electroporation and then incubated with Hela cervical cancer cells for 24 hours. TGF-beta, SMAD, Snail, Slug, beta-catenin, Notch, Caspase-3, Caspase-9, Bax, Bcl-2 protein and gene expression levels were analyzed in Hela cells. As a result, low concentration Exo-PAC induced apoptosis, and suppressed epithelial-mesenchymal transition proteins in Hela cells. In this study, it has been demonstrated that WJ-MSCs can be used as drug delivery systems for cervical cancer if exosomes are produced scalably in the future.